2017
DOI: 10.47264/idea.lassij/1.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Academic Achievements of Students in Mathematics

Abstract: This study is conducted to find out the factors which are associated with students’ academic achievements in the subject of mathematics in different higher education institutions which are based in Peshawar, Khyber Pakhtunkhwa, Pakistan. The data is collected through a structured questionnaire from Bachelor of Studies (BS) 5th semester program of all the academic departments of well-known government educational institutions of Peshawar. All academic departments, except the departments of mathematics were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Wästlund et al (2015) found that Namibian grade 12 learners were unable to solve non-routine problems due to their comprehension and language problems and also low knowledge about the strategies, so they faced problems in solving tasks. For teaching and learning mathematics problem-solving phase is very crucial (Abdullah et al, 2019;Ullah et al, 2017). Břehovský ( 2013) describe heuristic ability as a problem-solving skill that possibly makes a shortcut to reach the goal or may lead to the desired solution of the problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wästlund et al (2015) found that Namibian grade 12 learners were unable to solve non-routine problems due to their comprehension and language problems and also low knowledge about the strategies, so they faced problems in solving tasks. For teaching and learning mathematics problem-solving phase is very crucial (Abdullah et al, 2019;Ullah et al, 2017). Břehovský ( 2013) describe heuristic ability as a problem-solving skill that possibly makes a shortcut to reach the goal or may lead to the desired solution of the problem.…”
Section: Literature Reviewmentioning
confidence: 99%